2021
DOI: 10.1016/j.isci.2021.102852
|View full text |Cite|
|
Sign up to set email alerts
|

The amyloid-inhibiting NCAM-PrP peptide targets Aβ peptide aggregation in membrane-mimetic environments

Abstract: Summary Substantial research efforts have gone into elucidating the role of protein misfolding and self-assembly in the onset and progression of Alzheimer’s disease (AD). Aggregation of the Amyloid-β (Aβ) peptide into insoluble fibrils is closely associated with AD. Here, we use biophysical techniques to study a peptide-based approach to target Aβ amyloid aggregation. A peptide construct, NCAM-PrP, consists of a largely hydrophobic signal sequence linked to a positively charged hexapeptide. The NCAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 96 publications
4
17
0
Order By: Relevance
“…A second finding is that NCAM1-PrP promotes the aggregation of the protein S100A9 by destabilizing the native structure and creating a misfolded state. 54 It has therefore been suggested that NCAM1-PrP unfolds or dissolves structured proteins by interaction with amyloidogenic sequences, 39 which is in line with our proposal that NCAM1-PrP is able to destabilize Aβ fibrils. for the mixed sample; E: optical phase at 1587 cm −1 ; F: optical phase at 1587 cm −1 minus optical phase at 1629 cm −1 overlayed with a height image.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…A second finding is that NCAM1-PrP promotes the aggregation of the protein S100A9 by destabilizing the native structure and creating a misfolded state. 54 It has therefore been suggested that NCAM1-PrP unfolds or dissolves structured proteins by interaction with amyloidogenic sequences, 39 which is in line with our proposal that NCAM1-PrP is able to destabilize Aβ fibrils. for the mixed sample; E: optical phase at 1587 cm −1 ; F: optical phase at 1587 cm −1 minus optical phase at 1629 cm −1 overlayed with a height image.…”
Section: Resultssupporting
confidence: 89%
“…Our interpretation is in line with previous findings. NCAM1-PrP was found to inhibit secondary nucleation of Aβ in a similar way as BRICHOS, 39 which is known to coat fibrils and thus prevents the surface-catalyzed formation of new fibrils. 55 The analogous action of NCAM1-PrP thus suggests that it can bind to Aβ fibrils and the mixed composition of the fibrils in our Aβ:NCAM1-PrP images supports this view.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…From the stock solutions, 20 μM, 100 μM, or 1 mM concentrations of peptides were prepared by dissolving in 100 mM Ammonium Acetate, pH 7. Ammonium acetate was widely used as a buffer for amyloid peptides’ aggregation [ 39 , 40 ]. Hence, we have chosen ammonium acetate as the buffer for our studies.…”
Section: Methodsmentioning
confidence: 99%